Epistemological approaches on the relationship between didactic pragmatism and pragmatic didacticism in the teaching-learning-assessment of economic disciplines - Marius Costel Esi (Association of Social and Educational Innovation, 2016)
The paradigms specific to the educational activity are susceptible of a number of explanations more or less pragmatic in the current educational system. Thus, the knowable structures found at the level of the learning process may be subjected to a review of an epistemological nature. In these conditions, the excessive meta theorization must be eliminated in practice. Moreover, to the extent that we take a methodological approach, we must take into consideration new strategies of teaching-learning-assessment. In these circumstances, our analysis focuses on the teaching approach in the field of economic disciplines. We are interested to see to what extent such a demarche becomes operational and acquire a pragmatic value to the teaching activity. Therefore, the learning situations judicious analysis highlights a number of aspects of a pragmatic nature in teaching.